Therapeutic computer software for occupational therapy: ways forward. - Seale JK (British Journal of Therapy & Rehabilitation, 1996)
A major obstruction to effective computer use with clients is a lack of therapeutically appropriate software. Attempts to obtain appropriate software include employing computer programmers or using authoring tools, both of which have problems that need to be overcome.